Novel preparation method and application of FeS nano material

Nanoferrous sulfide material prepared by a new preparation method solves the problem of insufficient adsorption capacity of existing FeS on Cr(VI), significantly improves the removal efficiency and reduces the risk of Cr(VI) regeneration, and achieves a more efficient and stable pollutant removal effect.

CN119750658APending Publication Date: 2025-04-04NANKAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510033342.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the prior art, the original FeS has insufficient adsorption capacity of oxygen-containing anionic pollutants (such as Cr), resulting in low removal efficiency, and the product after FeS reacts with Cr(VI) is easily regenerated into Cr(VI) in the environment, increasing environmental risks.

Method used

A new preparation method is used to prepare nanoferrous sulfide materials. By stirring a mixed solution of FeCl3 solution and NaBH4 and Na2S2O4 under a nitrogen environment, FeS nanoparticles are formed, and their purity and stability are improved through high-speed centrifugation and multiple washings.

Benefits of technology

The adsorption capacity and removal efficiency of FeS on Cr(VI) are improved, the rate of Cr(VI) regeneration in the environment is reduced, and the safety risks to the human body and the ecology are significantly reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750658A_ABST
    Figure CN119750658A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of nano material preparation and underground water heavy metal pollution remediation, and particularly relates to a novel preparation method and application of a nano ferrous sulfide material. The preparation method provided by the invention is simple and easy to operate, NaBH4 and Na2S2O4 are mainly used as a reducing agent and a sulfur source in a system, and FeCl3. 6H2O prepared from deoxidized deionized water is used as an iron source; by regulating and controlling the addition amount of the iron source and the sulfur source, the iron sulfide with different coordination environments is successfully prepared. The prepared low-coordination ferrous sulfide has extremely high removal capacity on hexavalent chromium, and meanwhile, the occurrence of hexavalent chromium pollution rebound can be effectively inhibited. Valuable reference is provided for optimization design and synthesis of follow-up nano repair materials, and health risks caused by oxygen-containing anion pollutants to human body and ecological safety can be effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of groundwater treatment, and in particular to a novel preparation method of nano ferrous sulfide material and application thereof. Background Art

[0003] Pollutant remediation technologies mainly include ex situ remediation technology and in situ remediation technology. In the process of pollutant remediation, the remediation of underground aquifers is the most challenging. Ex situ remediation technology has the defects of high cost and low efficiency, while in situ remediation technology has the problem of being difficult due to factors such as slow mass transfer rate and low reaction efficiency. Therefore, it is urgent to develop a green, efficient and economical remediation technology that can be used for underground aquifers in contaminated sites. At present, the in situ remediation technologies used for soil-groundwater heavy metal contaminated sites are mainly solidification / stabilization and chemical oxidation / reduction. Among them, iron-based materials (such as nZVI, S-nZVI, FeS) are the most widely used in situ reduction agents. Nano ferrous sulfide (FeS), as a very promising engineering nanoremediation material, has been widely used in environmental remediation and hazardous waste treatment. FeS is a highly efficient reducing agent. Since Fe(Ⅱ) and S(-Ⅱ) can act as electron donors, FeS has a good treatment effect on common pollutants in soil and groundwater, such as Hg, Cr(Ⅵ) and As. However, there are still environmental risks in its actual application process. Taking chromium pollution as an example, many chromium-contaminated sites at home and abroad have Cr as the reaction product after iron-based material repair. x Fe 1-x (OH)3 is often reoxidized to Cr(VI), which again poses a secondary environmental risk. This limits its role in environmental remediation. Therefore, FeS nanoparticles must be optimized to increase their stability, mobility, and reactivity. Summary of the invention

[0004] Based on the shortcomings of the prior art, the technical problem to be solved by the present invention is to improve the adsorption capacity of the original FeS in the prior art for oxygen-containing anion pollutants (such as Cr), thereby improving the removal efficiency and reducing the product (Cr) after the reaction of FeS and Cr (VI). x Fe 1-x (OH)3) can reduce the regeneration rate of Cr(VI) in the environment, thereby minimizing the risk of Cr(VI) to human body and ecological safety.

[0005] The technical solution of the present invention is as follows:

[0006] A novel preparation method of nano ferrous sulfide material comprises the following steps:

[0007] 1) Under the condition of nitrogen gas, 8-12 g / L FeCl3·6H2O was prepared with deoxygenated deionized water and stirred to form a uniform solution;

[0008] 2) In a container that does not react with NaBH4 and Na2S2O4, prepare NaBH4 and Na2S2O4 by stirring. 4的 A homogeneous solution was prepared, wherein the concentration of NaBH4 ranged from 27.2 to 40.8 g / L and the concentration of Na2S2O4 ranged from 11 to 44 g / L;

[0009] 3) Under stirring with a stirring paddle, drop the mixed solution of NaBH4 and Na2S2O4 in 2) into the FeCl3·6H2O solution in 1) until the solution turns black. In this reaction system, continue stirring for 20-40 minutes;

[0010] 4) After the reaction is completed, centrifuge at 7000-10000 rpm using a high-speed centrifuge to obtain the generated precipitate, and wash it repeatedly in an anaerobic box using deoxygenated water;

[0011] 5) The washed precipitate is placed in a freeze dryer and stored in an anaerobic box after drying.

[0012] The deoxygenated deionized water is prepared by using high-purity nitrogen gas, the purity of which must be higher than 99.99%. The deionized water is deoxygenated for at least 1 hour.

[0013] The container of step 2) is a three-mouth container, wherein the three mouths include a nitrogen inlet, an agitator inlet and a dripping port.

[0014] The stirring rate of step 2) is 350-450 rpm.

[0015] The dripping rate of step 3) is 7-10 ml / min.

[0016] The step 4) is centrifuged for 5-10 minutes to obtain the generated precipitate product, and the precipitate product is repeatedly washed 4-6 times in an anaerobic box using the deoxygenated water in 1).

[0017] The step 5) is dried for 12-24 hours; the drying includes at least one of freeze drying and vacuum freeze drying.

[0018] Application of the nano ferrous sulfide material prepared by the preparation method of the present invention in in-situ remediation of groundwater containing Cr(VI).

[0019] The nano ferrous sulfide material prepared by the preparation method of the present invention is used to resist chromium pollution rebound after in-situ repair of groundwater containing Cr(VI).

[0020] At present, there are biological treatment, chemical precipitation, electrolytic reduction, adsorption and other methods for the removal of Cr(VI). Among them, the adsorption method has good removal effect, simple operation, low cost, and most importantly, no new pollutants are introduced in the wastewater treatment process. The following will introduce the application principle and characterization method of the main application materials (nano zero-valent iron, sulfide nano zero-valent iron and ferrous sulfide) of the embodiments of this specification (FeS prepared by the new synthesis method) and the comparative example to remove Cr(VI) pollution, in order to illustrate that the FeS prepared by the new synthesis method improves the Cr(VI) removal efficiency of the existing materials (nano zero-valent iron, sulfide nano zero-valent iron and ferrous sulfide) while greatly reducing the regeneration rate of Cr(VI).

[0021] (1) Cr(VI) removal application principle:

[0022] Nano zero-valent iron (nZVI): It has a large specific surface area and extremely strong reduction activity, and is a commonly used nanomaterial in the field of environmental remediation. The high reactivity of nZVI can quickly reduce Cr(VI) to Cr(III), but in actual use, nZVI is prone to agglomeration and oxidation, which greatly reduces its reduction effect on Cr(VI).

[0023] Ferrous sulfide (FeS): It is a tetragonal iron-based material with high specific surface area and multiple active sites. It contains two reducing ions, Fe(Ⅱ) and S(-Ⅱ), which can act as electron donors to reduce Cr(VI).

[0024] (2) Cr(VI) regeneration mechanism:

[0025] Changes in redox conditions can affect the "redissolution" of hexavalent chromium (i.e., the occurrence of chromium pollution rebound). The original trivalent chromium in the contaminated soil or the trivalent chromium formed by reduction treatment will be oxidized or reoxidized to hexavalent chromium when the redox properties of the environment change (such as the introduction of oxidants by humans and the widespread presence of manganese oxides in the background strata, etc.), causing hexavalent chromium pollution to "rebound". Sulfur iron salts (such as FeS, FeS2, etc.) are often used as hexavalent chromium pollution remediation agents, which can reduce hexavalent chromium to Cr-Fe co-precipitate Cr x Fe 1-x (OH) 3。 Studies have shown that trivalent chromium can be converted into hexavalent chromium through molecular oxygen, hydrogen peroxide, sulfite, and catalytic oxidation of Mn(II). Especially under alkaline conditions, a very small amount of hydrogen peroxide will promote the "re-dissolution" of hexavalent chromium.

[0026] (3) FeS prepared by the new synthesis method improves the Cr(VI) removal efficiency while reducing the Cr(VI) regeneration rate:

[0027] In order to explore the removal mechanism of Cr(VI) and the mechanism affecting the long-term adsorption, pH effect experiments, Cr(VI) adsorption experiments, and long-term experiments under the influence of coexisting anions and in-situ chemical oxidation technology were carried out. A certain amount of K2Cr2O7 was weighed to prepare a Cr(VI) solution with a mass concentration of 500 mg / L as a stock solution, and then the adsorption experiment was carried out by diluting the stock solution. A 1M sulfite solution and a 1M H2O2 solution were prepared as the stock solution for the oxidation rebound experiment, and then the oxidation rebound experiment was carried out by diluting the stock solution. The Cr(VI) concentration in the adsorption solution was determined by UV-visible photometer according to the national standard GB7467-1987 "Determination of hexavalent chromium in water quality-diphenylcarbazide spectrophotometry", and the adsorption amount (qt) of Cr(VI) was calculated. The total chromium content was determined by inductively coupled plasma ICP-MS, and the Cr(III) content was calculated by the difference method. The crystal phase changes of the materials at various stages in the pH influence experiment, Cr(VI) adsorption experiment, and long-term effect experiment under the influence of coexisting anions and in-situ chemical oxidation technology were monitored by material characterization methods such as XRD / XPS, and the feasibility of the embodiment was demonstrated by the unique crystal phase change trend of the embodiment material.

[0028] Under aerobic conditions of 100mM-H2O2, samples were taken regularly to monitor whether Cr(III) was reoxidized to Cr(VI). XPS and XRD characterizations were used to detect the stability of the resulting products. XPS characterization was used to detect whether the new synthesis method of nano-ferrous sulfide materials changed the Fe2p1 / 2 peak position and the peak distance between Fe2p1 / 2 and Fe2p3 / 2. Compared with the original FeS, the peak distance between Fe2p1 / 2 and Fe2p3 / 2 increased, thereby affecting the atomic coordination and band structure changes of Fe in FeS. , whether the iron coordination number is reduced compared with the original FeS, so as to reduce the coordination capacity of iron in the material, thereby corresponding to its excellent Cr(VI) adsorption capacity and long-term adsorption in the test example; through the XRD data monitoring of the reaction material after the long-term experiment under the influence of coexisting anions and the in-situ chemical oxidation technology, compared with the zero-valent iron material, whether the XRD structure of the nano-ferrous sulfide material prepared by the new synthesis method tends to generate a more stable and more adsorbable iron hydroxide oxidized crystal phase, rather than a hydroxide and iron oxide crystal phase with weaker adsorption capacity. It is hoped that the above-mentioned characterization means will prove that the FeS material prepared by the synthesis method has excellent Cr(VI) pollution removal ability and has great application prospects in the research direction of anti-chromium pollution rebound.

[0029] Advantages and excellent effects of the present invention

[0030] 1) The FeS nanomaterial provided by the present invention has the advantages of high repeatability and no secondary pollution;

[0031] 2) The present invention effectively adjusts the atomic coordination and energy band structure of the original FeS through a simple co-precipitation synthesis process. XPS analysis shows that the synthesis method reduces the coordination ability of Fe, enhances the adsorption of Cr(VI) by improving the chemical complexation between the original FeS and Cr(VI), and thus improves the overall removal efficiency of Cr(VI).

[0032] 3) Compared with loading or encapsulating FeS in porous materials (carbon materials, zeolites, molecular sieves, metal organic frameworks, covalent organic frameworks), the present invention has lower economic cost and operability, better compatibility in the environment, and is in line with the concept of green and sustainable development. The price of raw materials will vary according to factors such as market supply and demand, purity requirements, and procurement channels. Generally speaking, the price of high-purity raw materials is relatively high, and the following calculation is selected from the average price of the reagent platform. The synthesis process of FeS loading or encapsulation in porous materials involves the complexity of the synthesis process, energy consumption, and reagent cost costs, such as energy (such as electricity, gas, etc.) and reagents (such as solvents, catalysts, etc.) consumed during the synthesis process, solution preparation, mixing, heating reaction, filtration washing, drying, etc. The complexity of these steps and the required equipment investment are all included in the production cost. Based on the above production costs, it is estimated that the production cost of FeS synthesized by this new preparation method is about 3-4 yuan / 0.1g; the production cost of porous materials (carbon materials, zeolites, molecular sieves, metal organic frameworks, covalent organic frameworks) is about 7-20 yuan / 0.1g; in addition, the porous material loaded with FeS

[0033] The high production cost also includes complex load operation, which greatly increases the economic cost and operation time.

[0034] 4) By adjusting the molar ratio between the Fe source and the S source, the present invention can obtain a nanomaterial with both a high Cr(VI) removal rate and a low Cr(VI) regeneration rate, greatly reducing the environmental risks caused by oxygen-containing anions Cr(VI). Experiments have shown that its anti-rebound ability is better than the current mainstream iron-based materials (nZVI, S-nZVI, FeS) for in-situ groundwater remediation. When the addition amount of Na2S2O4 is 11g / L and Fe 3+ When the addition amount is 8 g / L, the synthesized material is named Example 1. When the addition amount of Na2S2O4 is 22 g / L, Fe 3 + When the addition amount is 10 g / L, the synthesized material is named Example 2. When the addition amount of Na2S2O4 is 44 g / L, Fe 3+ When the addition amount is 12 g / L, the synthesized material is named Example 3. Experimental verification shows that the Cr(VI) removal effect of the example is better than that of the comparative example, which proves that FeS prepared by the new synthesis method has the greatest application prospect in the application of Cr(VI) pollutant removal and anti-rebound. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 X-ray diffraction spectra of FeS nanomaterials (FeS, Example 1, Example 2, Example 3)

[0036] Figure 2 .nZVI / S-nZVI / FeS and ferrous sulfide nanomaterials prepared by a novel synthesis method (Example 1, Example 2, Example 3) Chromium fixation in anaerobic system

[0037] Figure 3 .100mM-SO3 2- Investigation of the regeneration of Cr(VI) by FeS nanomaterials (FeS, Example 1, Example 2, Example 3) under aerobic conditions

[0038] Figure 4 .100mM-H2O2, FeS nanomaterials (FeS, Example 1, Example 2, Example 3) under aerobic conditions to investigate the regeneration of Cr (VI)

[0039] Figure 5 Investigation of Cr(VI) regeneration under aerobic conditions using 100mM-H2O2, nZVI / S-nZVI / FeS and ferrous sulfide nanomaterials prepared by a novel synthesis method (Example 2)

[0040] Figure 6 Monitoring of Cr(VI) regeneration in real groundwater samples after 30 days of reaction with 100mM-H2O2, nZVI / S-nZVI / FeS and ferrous sulfide nanomaterials prepared by a novel synthesis method (Example 2)

[0041] Figure 7 XPS characterization of nZVI / S-nZVI / FeS and ferrous sulfide nanomaterials prepared by a novel synthesis method (Example 1, Example 2, Example 3)

[0042] Figure 8 .100mM-SO3 2- XRD characterization of ferrous sulfide nanomaterials prepared by rebound reaction of nZVI / FeS and novel synthesis method under 100mM-H2O2 (Example 2) DETAILED DESCRIPTION

[0043] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0044] A novel preparation method of nano ferrous sulfide material comprises the following steps:

[0045] 1) Deionized water is deoxygenated using high-purity nitrogen (nitrogen purity must be higher than 99.99%, i.e., the purity range is 99.99%-99.999%) for at least 1 hour. This deoxygenated deionized water is used for subsequent washing of the precipitate;

[0046] 2) In a three-necked container (any material that does not react with the added reagents can be used), nitrogen is introduced into one neck opening, a constant pressure dropping funnel is installed at the other neck opening (or a speed-adjustable peristaltic pump is connected), a two-blade stirring paddle is inserted through the middle neck opening for stirring (or a magnetic stirrer is used in an anaerobic chamber), and a uniform solution of 8-12 g / L FeCl3·6H2O is prepared using the deoxygenated water in 1);

[0047] 3) In a beaker (or other container that does not react with NaBH4 and Na2S2O4) with a volume of 250-500 ml, a mixed uniform solution of NaBH4 and Na2S2O4 (wherein the concentration of NaBH4 is 27.2-40.8 g / L and the concentration of Na2S2O4 is 11-44 g / L) is prepared by magnetic stirring (or stirring with a stirring paddle);

[0048] 4) Under stirring with a two-blade stirring paddle (350-450rpm), pour the mixed solution of 27.2-40.8g / L NaBH4 and 11-44g / L Na2S2O4 in 3) into a constant pressure dropping funnel (or connect to a speed-adjustable peristaltic pump to flow at a constant speed through the peristaltic pump), and drip into the FeCl3·6H2O uniform solution in 2) at a rate of 7-10ml / min. At this time, it can be found that the original solution quickly turns black, indicating that a large amount of FeS is generated instantly. Then, in this reaction system, continue stirring for 20-40min. The above reaction temperatures are all room temperature;

[0049] 5) After the reaction is completed for 20-40 minutes, centrifuge at 7000-10000 rpm for 5-10 minutes to obtain the generated precipitate, and wash it repeatedly in an anaerobic box with the deoxygenated water in 1) for 4-6 times;

[0050] 6) The washed precipitate is placed in a freeze dryer, dried for 12-24 hours, and then stored in an anaerobic chamber.

[0051] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0052] Example 1

[0053] 1) Deionized water is deoxygenated using high-purity nitrogen (purity range is 99.99%-99.999%) for 1.5 hours, and the deoxygenated deionized water is used for subsequent washing of the precipitate;

[0054] 2) In a three-necked container, nitrogen is introduced into one neck opening, a constant pressure dropping funnel is installed at the other neck opening, and a two-blade stirring paddle is inserted through the middle neck opening to stir, thereby preparing 200 ml of a uniform solution containing 8 g / L FeCl3·6H2O. This solution is prepared using the deoxygenated water in 1);

[0055] 3) In a 250 ml container, prepare 200 ml of a mixed homogeneous solution containing 27.2 g / L NaBH4 and 11 g / L Na2S2O4 by magnetic stirring;

[0056] 4) Under the stirring of a two-blade stirring paddle (350rpm), pour a mixed homogeneous solution of 27.2g / L NaBH4 and 11g / L Na2S2O4 into a constant pressure dropping funnel and drip into the homogeneous FeCl3·6H2O solution at a rate of 7ml / min. At this time, it can be found that the original solution quickly turns black, indicating that a large amount of FeS is generated instantly. Then, in this reaction system, stirring is continued for 20min. The above reaction temperatures are all at room temperature;

[0057] 5) After the reaction was completed for 20 minutes, the mixture was centrifuged at 8000 rpm for 5 minutes using a high-speed centrifuge to obtain the precipitated product, which was then washed four times in an anaerobic box using deoxygenated water;

[0058] 6) The washed precipitate was placed in a freeze dryer, dried for 12 hours, and then stored in an anaerobic chamber.

[0059] Embodiment 1 Description of the accompanying drawings:

[0060] Depend on Figure 1 It can be seen that the new synthesis method in Example 1 causes the characteristic peaks (001) and (112) of FeS to shift, indicating that the molar ratio of Fe and S may induce residual stress in the nanomaterial. The left shift of the characteristic peak also means that the unit cell spacing of the material may expand and the lattice spacing increases.

[0061] Depend on Figure 2 It can be seen that under anaerobic conditions, compared with the original FeS, the nano-FeS in Example 1 has a better removal effect on Cr(VI), that is, all the liquid phase Cr(VI) is removed in the water phase, and it can be reduced to solid phase Cr(III) to the greatest extent, and its removal effect is better than that of zero-valent iron and sulfide nano-zero-valent iron, indicating that the FeS prepared by this synthesis method has great application potential in the field of Cr(VI) pollution removal.

[0062] Combination Figure 2 , Figure 3 , Figure 4 , Figure 5 It can be seen that for the original FeS and other novel synthesis methods to prepare FeS nanomaterials with different S / Fe molar ratios, in the same time period, the introduction of 100mM sulfite oxidant for monitoring for 90 days, the rebound rates of FeS and Example 1 were 3.40% and 0.00%, respectively; the introduction of 100mM hydrogen peroxide oxidant for monitoring for 30 days, the rebound rates of nZVI, S-nZVI, original FeS, and Example 1 were 92.34%, 31.87%, 50.24%, and 6.11%, respectively, proving that the synthesis method prepared the example FeS material The long-term effectiveness of the material under the influence of coexisting anions and in-situ chemical oxidation technology is better than that of nZVI / S-nZVI / original FeS material. It is also worth noting that the material Example 1, which performs well under anaerobic conditions, still has a lower rebound rate than the original FeS under aerobic conditions of 100mM-H2O2, indicating that it not only has a higher removal efficiency, but also has a higher stability of the resulting product. This proves that the FeS material prepared by the synthesis method has excellent Cr(VI) pollution removal ability and has great application prospects in the research direction of anti-chromium pollution rebound.

[0063] Depend on Figure 7 It can be seen that the XPS characterization of nZVI / S-nZVI / FeS and the ferrous sulfide nanomaterial Example 1 prepared by the new synthesis method shows that the new synthesis method of the nano ferrous sulfide material changes the Fe2p1 / 2 peak position and the peak spacing between Fe2p1 / 2 and Fe2p3 / 2. Compared with the original FeS, the peak spacing between Fe2p1 / 2 and Fe2p3 / 2 in Example 1 is increased, which in turn affects the atomic coordination and band structure changes of Fe in FeS. Among them, the iron coordination number of the nano ferrous sulfide material Example 1 prepared by the new synthesis method is reduced compared with the original FeS, which reduces the coordination ability of iron in the material, corresponding to its excellent Cr(VI) adsorption capacity and long-term adsorption in the test example.

[0064] Example 2

[0065] 1) Deionized water is deoxygenated using high-purity nitrogen (purity range is 99.99%-99.999%) for 1.5 hours, and the deoxygenated deionized water is used for subsequent washing of the precipitate;

[0066] 2) In a three-necked container, nitrogen is introduced into one neck opening, a constant pressure dropping funnel is installed at the other neck opening, and a two-blade stirring paddle is inserted through the middle neck opening to stir, thereby preparing 200 ml of a uniform solution containing 10 g / L FeCl3·6H2O. This solution is prepared using the deoxygenated water in 1);

[0067] 3) In a 300 ml container, prepare 200 ml of a mixed homogeneous solution containing 34 g / L NaBH4 and 22 g / L Na2S2O4 by magnetic stirring;

[0068] 4) Under the stirring of a two-blade stirring paddle (400 rpm), pour a mixed homogeneous solution of 34 g / L NaBH4 and 22 g / L Na2S2O4 into a constant pressure dropping funnel, and drop it into the homogeneous FeCl3·6H2O solution at a rate of 8 ml / min. At this time, it can be found that the original solution quickly turns black, indicating that a large amount of FeS is generated instantly. Then, in this reaction system, stirring is continued for 30 minutes. The above reaction temperatures are all room temperature;

[0069] 5) After the reaction was completed for 30 min, the mixture was centrifuged at 8000 rpm for 8 min to obtain the precipitated product, which was then washed repeatedly 5 times in an anaerobic box with deoxygenated water;

[0070] 6) The washed precipitate was placed in a freeze dryer, dried for 20 hours, and then stored in an anaerobic chamber.

[0071] Embodiment 2 Description of the drawings:

[0072] Depend on Figure 1 It can be seen that the new synthesis method in Example 2 causes the characteristic peaks (001) and (112) of FeS to shift, indicating that the molar ratio of Fe and S may induce residual stress in the nanomaterial. The left shift of the characteristic peak also means that the material unit cell spacing may expand and the lattice spacing increases.

[0073] Depend on Figure 2 It can be seen that under anaerobic conditions, compared with nZVI, S-nZVI and original FeS, the nano-FeS in Example 2 has the best removal effect on Cr(VI), that is, all liquid Cr(VI) is removed in the aqueous phase, and it can be reduced to solid Cr(III) to the greatest extent, and its removal effect is better than that of zero-valent iron and sulfide nano-zero-valent iron, indicating that the FeS prepared by this synthesis method has great application potential in the field of Cr(VI) pollution removal.

[0074] Combination Figure 2 , Figure 3 , Figure 4It can be seen that for the original FeS and other FeS nanomaterials with different S / Fe molar ratios prepared by the new synthesis method, in the same time period, 100mM sulfite oxidant was introduced for monitoring for 90 days, and the rebound rates of FeS and Example 2 were 3.40% and 0.94%, respectively; 100mM hydrogen peroxide oxidant was introduced for monitoring for 30 days, and the rebound rates of FeS and Example 2 were 50.24% and 2.64%, respectively, proving that the long-term effectiveness of the example FeS material prepared by the synthesis method under the influence of coexisting anions and in-situ chemical oxidation technology is better than that of the original FeS material. It is also worth noting that the material Example 2, which performs well under anaerobic conditions, has a lower rebound rate than the original FeS under aerobic conditions of 100mM-H2O2, indicating that it not only has a higher removal efficiency, but also the stability of the product obtained is higher, proving that the example FeS material prepared by the synthesis method has excellent Cr(VI) pollution removal ability and has great application prospects in the research direction of anti-chromium pollution rebound.

[0075] Combination Figure 2 , Figure 3 , Figure 5 It can be seen that for nZVI / S-nZVI / original FeS and the ferrous sulfide nanomaterial Example 2 prepared by the new synthesis method, in the same time period, 100mM hydrogen peroxide oxidation agent was introduced to monitor for 30 days, and the rebound rates of nZVI, S-nZVI, FeS, and Example 2 were 92.34%, 31.87%, 50.24%, and 2.64%, respectively, proving that the long-term effectiveness of the example FeS material prepared by the synthesis method under the influence of coexisting anions and in-situ chemical oxidation technology is better than that of nZVI / S-nZVI / original FeS material. It is also worth noting that the material Example 2, which performs best under anaerobic conditions, still has almost no oxidization of Cr(III) to Cr(VI) under aerobic conditions of 100mM-H2O2, indicating that it not only has a higher removal efficiency, but also has a higher stability of the product obtained, proving that the example FeS material prepared by the synthesis method has excellent Cr(VI) pollution removal ability and has great application prospects in the research direction of anti-chromium pollution rebound.

[0076] Depend on Figure 6It can be seen that for nZVI, S-nZVI, FeS and Example 2, in the same time period, real groundwater samples were taken in Liandu District, Lishui City, Zhejiang Province, China (28°23′35″N, 119°50′39″E), and the monitoring results showed that there was no Cr(VI) exceeding the standard in the groundwater in the area. A quantitative groundwater sample was added with potassium dichromate to prepare a groundwater sample containing 50 mg / L-Cr(VI). The pH of the solution was adjusted to 3, 5, 7, 9, and 11 with hydrochloric acid and sodium hydroxide, respectively. A 100 mM hydrogen peroxide oxidation agent was introduced for monitoring for 30 days. nZVI , S-nZVI, FeS, and Example 2 all monitored the highest rebound data during the 30-day period, and the rebound rates of their aerobic rebound reactions when the groundwater's normal pH value was 7 were 1.36%, 29.24%, 9.64%, and 1.18%, respectively, and when the groundwater's extreme pH value was 11, the rebound rates were 56.48%, 44.65%, 72.29%, and 4.66%, respectively. The material with the best overall performance was still Example 2, indicating that the Example FeS prepared by the synthesis method had higher material stability under various pH conditions, and had great application prospects in the research direction of anti-chromium pollution rebound.

[0077] Depend on Figure 7 It can be seen that the XPS characterization of nZVI / S-nZVI / FeS and Example 2 prepared by the new synthesis method shows that the new synthesis method of nano-ferrous sulfide material changes the Fe2p1 / 2 peak position and the peak distance between Fe2p1 / 2 and Fe2p3 / 2. Compared with the original FeS, the peak distance between Fe2p1 / 2 and Fe2p3 / 2 in Example 2 is increased, which in turn affects the atomic coordination and band structure changes of Fe in FeS. Among them, the iron coordination number of Example 2 of nano-ferrous sulfide material prepared by the new synthesis method is reduced compared with the original FeS, which reduces the coordination ability of iron in the material, corresponding to its excellent Cr(VI) adsorption capacity and long-term adsorption in the test example.

[0078] Depend on Figure 8 It can be seen that the XRD data of the reaction material after the long-term experiment under the influence of coexisting anions and in-situ chemical oxidation technology showed obvious changes. Compared with the zero-valent iron material, the XRD structure of the material in Example 2 tends to generate a more stable and more adsorbable hydroxyl iron oxide crystal phase, rather than a hydroxide and iron oxide crystal phase with weaker adsorption capacity, which once again verifies the feasibility of the long-term adsorption effect of the example material.

[0079] Example 3

[0080] 1) Deionized water is deoxygenated using high-purity nitrogen (purity range is 99.99%-99.999%) for 1.5 hours, and the deoxygenated deionized water is used for subsequent washing of the precipitate;

[0081] 2) In a three-necked container, nitrogen is introduced into one neck opening, a constant pressure dropping funnel is installed at the other neck opening, and a two-blade stirring paddle is inserted through the middle neck opening to stir, thereby preparing 200 ml of a uniform solution containing 12 g / L FeCl3·6H2O. This solution is prepared using the deoxygenated water in 1);

[0082] 3) In a 500 ml container, prepare 200 ml of a mixed homogeneous solution containing 40.8 g / L NaBH4 and 44 g / L Na2S2O4 by magnetic stirring;

[0083] 4) Under stirring with a two-blade stirring paddle (450 rpm), pour a mixed homogeneous solution of 40.8 g / L NaBH4 and 44 g / L Na2S2O4 into a constant pressure dropping funnel and drip into the homogeneous FeCl3·6H2O solution at a rate of 10 ml / min. At this time, it can be found that the original solution quickly turns black, indicating that a large amount of FeS is generated instantly. Then, in this reaction system, stirring is continued for 40 minutes. The above reaction temperatures are all at room temperature;

[0084] 5) After the 40-min reaction was completed, the mixture was centrifuged at 8000 rpm for 10 min in a high-speed centrifuge to obtain the precipitated product, which was then washed repeatedly six times in an anaerobic box using deoxygenated water;

[0085] 6) The washed precipitate was placed in a freeze dryer, dried for 24 hours, and then stored in an anaerobic chamber.

[0086] It should be noted that the water and aqueous solution added during the preparation and washing process are deoxygenated. The deoxygenation treatment can be carried out using N2. All operations are carried out under the protection of N2. This setting can prevent ferrous salts from reacting with dissolved oxygen in water and oxidizing and deteriorating.

[0087] Embodiment 3 Description of the drawings:

[0088] Depend on Figure 1 It can be seen that the new synthesis method in Example 2 causes the characteristic peaks (001) and (112) of FeS to shift, indicating that the molar ratio of Fe and S may induce residual stress in the nanomaterial. The left shift of the characteristic peak also means that the material unit cell spacing may expand and the lattice spacing increases.

[0089] Depend on Figure 2 It can be seen that under anaerobic conditions, compared with nZVI, S-nZVI and original FeS, the nano-FeS in Example 2 has the best removal effect on Cr(VI), that is, all liquid Cr(VI) is removed in the aqueous phase, and it can be reduced to solid Cr(III) to the greatest extent, and its removal effect is better than that of zero-valent iron and sulfide nano-zero-valent iron, indicating that the FeS prepared by this synthesis method has great application potential in the field of Cr(VI) pollution removal.

[0090] Combination Figure 2 , Figure 3 , Figure 4 , Figure 5 It can be seen that for the original FeS and other new synthetic methods to prepare FeS nanomaterials with different S / Fe molar ratios, in the same time period, the introduction of 100mM sulfite oxidant for 90 days of monitoring, the rebound rates of FeS and Example 3 were 3.40% and 0.00%, respectively; the introduction of 100mM hydrogen peroxide oxidant for 30 days of monitoring, the rebound rates of nZVI, S-nZVI, FeS, and Example 3 were 92.34%, 31.87%, 50.24%, and 21.27%, respectively, proving that the synthetic method prepared Example FeS The long-term effectiveness of the material under the influence of coexisting anions and in-situ chemical oxidation technology is better than that of nZVI / S-nZVI / original FeS material. It is also worth noting that Example 3, which performs well under anaerobic conditions, has a lower rebound rate than the original FeS under aerobic conditions of 100mM-H2O2, indicating that it not only has a higher removal efficiency, but also the stability of the resulting product is higher. This proves that the example FeS material prepared by this synthesis method has excellent Cr(VI) pollution removal ability and has great application prospects in the research direction of anti-chromium pollution rebound.

[0091] Depend on Figure 7 It can be seen that the XPS characterization of nZVI / S-nZVI / FeS and Example 3 prepared by the new synthesis method shows that the new synthesis method of nano-ferrous sulfide material changes the Fe2p1 / 2 peak position and the peak distance between Fe2p1 / 2 and Fe2p3 / 2. Compared with the original FeS, the peak distance between Fe2p1 / 2 and Fe2p3 / 2 in Example 3 is increased, which in turn affects the atomic coordination and band structure changes of Fe in FeS. Among them, the iron coordination number of Example 3 of nano-ferrous sulfide material prepared by the new synthesis method is reduced compared with the original FeS, which reduces the coordination ability of iron in the material, corresponding to its excellent Cr(VI) adsorption capacity and long-term adsorption in the test example.

[0092] Comparative Example 1

[0093] Nano-zero-valent iron (nZVI): purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. (CAS: 7439-89-6).

[0094] Comparative Example 2

[0095] Sulfide nano-zero-valent iron (S-nZVI): The synthesis method is referred to the literature (doi: 10.1021 / acs.est.4c04466).

[0096] Comparative Example 3

[0097] Ferrous sulfide (FeS): purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. (specification: Fe, 60.0-72.0%).

[0098] Test Example 1

[0099] The removal effects of the modified nano-ferrous sulfide composite materials provided in Examples 1-3 (named as Example 1, Example 2, and Example 3, respectively), the nano-zero-valent iron (nZVI), sulfide nano-zero-valent iron (S-nZVI), and nano-ferrous sulfide (FeS) provided in Comparative Examples 1-3 on Cr(VI) in aqueous solutions were determined.

[0100] Detection method: All experiments were conducted in 250 mL glass bottles, in which 100 mL of deoxygenated water and 100 mL of 100 mg·L -1 The potassium dichromate solution (the potassium dichromate solution is prepared with deoxygenated water) was added, and the pH of the solution was adjusted to 7 with hydrochloric acid and sodium hydroxide. Then, 0.2 g of Example 1, Example 2, Example 3, nZVI, S-nZVI or FeS was added to the system. The glass bottle was placed in a constant temperature oscillating box (25°C, 180 r·min -1 ) was shaken for 180 min, and the mass concentration of Cr(VI) was determined by inductively coupled plasma mass spectrometry.

[0101] Test results such as Figure 2 As shown, compared with FeS and S-nZVI, the nano-ferrous sulfide materials provided in Examples 1-3 (Example 1, Example 2, Example 3) can completely remove Cr(VI) from the aqueous phase after anaerobic reaction for 24 hours, and reduce Cr(VI) to Cr(III) by nearly 100%, and the removal capacity of Cr(VI) is significantly improved.

[0102] Test Example 2

[0103] Long-term effect of heavy metal chromium stabilization products under the influence of coexisting anions: Based on previous research results and actual contaminated site remediation project case data, it was found that the concentrations of sulfate and sulfite in underground aquifers continued to increase under future development scenarios. Therefore, this section mainly studies the rebound of chromium pollution under the influence of sulfite. After chromium pollution stabilization for 24 hours, adjust the pH to 7 with NaOH and HCl solution, and add a certain amount of Na2SO3. SO3 in the entire reaction system 2-The concentrations were set to 5mM, 20mM, and 100mM, and then 4mL of the reaction solution was accurately measured with a pipette and placed in a series of 10mL glass vials. After sealing with a single-layer sealing film, the vials were placed in a constant temperature shaker for shaking and mixing. Samples were then taken at 24h, 72h, 168h, 240h, 480h, 720h, 1440h and 2160h. The Cr(VI) content in the solution and on the solid surface was then determined using an ELISA reader and ICP-MS to calculate the pollution rebound rate of different remediation technologies under dissolved oxygen conditions.

[0104] Combination Figure 2 , Figure 3 It can be seen that for the original FeS and the nanomaterials prepared by the new synthesis method, in the same time period, 100 mM sulfite oxidant was introduced and monitored for 90 days, and the rebound rates of FeS, Example 1, Example 2, and Example 3 were 3.40%, 0.00%, 0.94%, and 0.00%, respectively.

[0105] Test Example 3

[0106] Long-term effectiveness of heavy metal chromium stabilization products under the influence of in-situ chemical oxidation technology: In-situ chemical oxidation is an effective means to repair organic contaminated sites. H2O2 is widely used in actual contaminated site remediation due to its good oxidation activity and environmental friendliness. Considering that the concentration of H2O2 produced by changes in natural conditions in the environmental system is at the micromolar level, while the concentration of the pollution remediation system can be as high as the molar level, therefore, under the H2O2 research system, referring to the operating procedures of the above-mentioned rebound experiment, a certain volume of H2O2 solution is added to the stabilized and repaired reaction solution, and the final concentration is set to 5mM, 20mM, and 100mM, and then divided into a series of 10mL glass vials and placed in a constant temperature shaker for shaking reaction. By sampling and quantitative analysis at different times, the rebound rate of chromium pollution under these conditions is obtained.

[0107] Combination Figure 2 , Figure 4 , Figure 5 It can be seen that for the original FeS and other nanomaterials with different S / Fe molar ratios, within the same time period, 20 mM hydrogen peroxide oxidation agent was introduced for monitoring for 30 days, and the rebound rates of FeS, Example 1, Example 2, and Example 3 were 4.11%, 4.76%, 1.53%, and 21.96%, respectively; 100 mM hydrogen peroxide oxidation agent was introduced for monitoring for 30 days, and the rebound rates of FeS, Example 1, Example 2, and Example 3 were 50.24%, 6.11%, 2.64%, and 21.27%, respectively.

[0108] Depend on Figure 6It can be seen that the degree of oxidative dissolution release of nZVI under different concentrations of H2O2 systems is higher than that of the other three nano-repairing agent systems, indicating that its stability is poor, and Example 2 shows the lowest rebound rate under any rebound inducement. It is also worth noting that Example 2, the material that performs best under anaerobic conditions, still has almost no oxidization of Cr(III) to Cr(VI) under aerobic conditions of 100mM-H2O2, indicating that it not only has a higher removal efficiency, but also the stability of the resulting product is higher, and has great application prospects in the research direction of anti-chromium pollution rebound.

[0109] The technical solutions disclosed and proposed in the present invention can be realized by those skilled in the art by referring to the contents of this article and appropriately changing the synthesis conditions and other links. Although the methods and preparation techniques of the present invention have been described through preferred embodiments, relevant technicians can obviously modify or re-combine the methods and technical routes described herein without departing from the content, spirit and scope of the present invention to realize the final preparation technology. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the spirit, scope and content of the present invention.

Claims

1. A novel preparation method of nano ferrous sulfide material, characterized in that: The following steps are involved: 1) Under the condition of nitrogen gas, 8-12 g / L FeCl3·6H2O was prepared with deoxygenated deionized water and stirred to form a uniform solution; 2) in a container that does not react with NaBH4 and Na2S2O4, a mixed uniform solution of NaBH4 and Na2S2O4 is prepared by stirring, wherein the concentration of NaBH4 is 27.2-40.8 g / L, and the concentration of Na2S2O4 is in the range of 11-44 g / L; 3) Under stirring with a stirring paddle, drop the mixed solution of NaBH4 and Na2S2O4 obtained in 2) into the FeCl3·6H2O solution obtained in 1), and the solution turns black. In this reaction system, continue stirring for 20-40 minutes; 4) After the reaction is completed, centrifuge at 7000-10000 rpm using a high-speed centrifuge to obtain the generated precipitate, and wash it repeatedly in an anaerobic box using deoxygenated water; 5) placing the washed precipitated product in a freeze dryer and drying it to obtain nano-ferrous sulfide material.

2. The preparation method according to claim 1, characterized in that: Deoxygenated deionized water is produced by using high-purity nitrogen gas, the purity of which must be higher than 99.99%. The deionized water is deoxygenated for at least 1 hour.

3. The preparation method according to claim 1, characterized in that: The container of step 2) is a three-mouth container, wherein the three mouths include a nitrogen inlet, an agitator inlet and a dripping port.

4. The preparation method according to claim 1, characterized in that: The stirring rate of step 2) is 350-450 rpm.

5. The preparation method according to claim 1, characterized in that: Step 3) The dripping rate is 7-10 ml / min.

6. The preparation method according to claim 1, characterized in that: Step 4) Centrifuge for 5-10 minutes to obtain the generated precipitate product, and wash it repeatedly 4-6 times in an anaerobic box using the deoxygenated water in step 1).

7. The preparation method according to claim 1, characterized in that: Step 5) drying for 12-24 hours; the drying includes at least one of freeze drying and vacuum freeze drying.

8. Use of the nano-ferrous sulfide material prepared by the preparation method of claim 1 in in-situ remediation of groundwater containing Cr(VI).

9. Application of the nano-ferrous sulfide material prepared by the preparation method of claim 1 to resist chromium pollution rebound after in-situ remediation of groundwater containing Cr(VI).